2022
DOI: 10.3390/ijerph19052886
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk of Job Instability and Unethical Organizational Behaviour Amid the COVID-19 Pandemic: The Role of Family Financial Pressure and Distributive Injustice in the Tourism Industry

Abstract: The economic disaster precipitated by the pandemic of COVID-19 changed people’s perceptions of ordinary job stability and elevated it to an ultimate high level. To avoid being laid off, employees who are concerned about job stability may engage in unethical activities in the name of their employer. In this study, the influence of job instability on unethical organizational behaviour (UOB) was investigated through the mediating role of family financial pressure and distributive injustice. Perceptions of 830 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…This finding contributes to the ever-expanding literature that proposes that the relationship between job insecurity and mental health is not straightforward and is influenced by a complex interplay of factors, including financial strain, social support, and coping resources [ 11 ]. Furthermore, the moderating influence of family financial pressures highlights the importance of considering employees’ broader life context when examining the impact of job insecurity on mental health [ 14 ]. This finding underscores the need for a holistic approach to employee wellbeing, one that considers not only work-related stressors but also broader life stressors that can impact mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding contributes to the ever-expanding literature that proposes that the relationship between job insecurity and mental health is not straightforward and is influenced by a complex interplay of factors, including financial strain, social support, and coping resources [ 11 ]. Furthermore, the moderating influence of family financial pressures highlights the importance of considering employees’ broader life context when examining the impact of job insecurity on mental health [ 14 ]. This finding underscores the need for a holistic approach to employee wellbeing, one that considers not only work-related stressors but also broader life stressors that can impact mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Job insecurity was quantified using six variables, three of which assessed its quantitative aspects and the other three evaluated its qualitative aspects. The questionnaire items were first proposed by [ 19 ] and later adopted by [ 14 ]. An example item for job insecurity is “I worry about losing my job” (with a reliability score of 0.951).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dichas circunstancias, pueden generar conflicto entre compañeros e influir negativamente en el clima laboral de la organización. 13 A pesar de que existe un predominio de nivel medio en la mayoría de los factores; se evidencia que el dominio de demandas de trabajo presenta un nivel de riesgo muy alto, lo que se puede constituir como un signo de alarma para la empresa y, a la vez, se puede ver afectada la satisfacción de los empleados. 14…”
Section: Discussionunclassified
“…Specifically, in a volatile marketplace where hotel employees feel worried about job loss, they reported higher anxiety (Aguiar-Quintana et al , 2021). Another research that focused on financial anxiety showed that perceived job risk instability heightened family financial pressure that, in turn, resulted in unethical organizational behavior (Elshaer et al , 2022). A study conducted by Peng et al (2022) documented that fear of COVID-19 gave rise to death anxiety that, in turn, triggered work alienation among hotel workers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%